2019
DOI: 10.33545/gynae.2019.v3.i4a.289
|View full text |Cite
|
Sign up to set email alerts
|

Role of intracervical foley's catheter as pre-induction cervical ripening agent in reducing rate of primary caesarean section

Abstract: Induction of labour may be required for various maternal or foetal reasons at times in the presence of poor Bishop's scoring. Cervical ripening is beneficial in these situations. A randomised comparative analysis was carried out using intracervical Foleys catheter instillation followed by a single dose of dinoprostone gel if required in one group and only dinoprostone gel for ripening in other group. Maternal and neonatal complications, mode of delivery and induction-delivery interval were assessed. We found a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 5 publications
8
2
0
Order By: Relevance
“…The mean time interval between time of induction and delivery was significantly lesser in Group 1 compared to Group 2 (14.63±3.42 hours vs. 15.73±2.20 hours; p<0.05). This is in concordance to the study of Malakar A et al, [1] where the induction-delivery interval in group A was 28.58 ± 7.54 hours and in group B it was 24.37 ±9.34 hours. This is comparable to the study of Murthy BK et al, [3] where Induction delivery interval was almost similar in the two groups (11.6 vs 11.1 in dinoprostone and Foleys catheter group respectively).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The mean time interval between time of induction and delivery was significantly lesser in Group 1 compared to Group 2 (14.63±3.42 hours vs. 15.73±2.20 hours; p<0.05). This is in concordance to the study of Malakar A et al, [1] where the induction-delivery interval in group A was 28.58 ± 7.54 hours and in group B it was 24.37 ±9.34 hours. This is comparable to the study of Murthy BK et al, [3] where Induction delivery interval was almost similar in the two groups (11.6 vs 11.1 in dinoprostone and Foleys catheter group respectively).…”
Section: Discussionsupporting
confidence: 93%
“…1.3% patient in Group 2 had BOH. This is consistent with the studies of Malakar A et al, [1] and Murmu S et al, [2]. Murmu S et al, [2] study observed commonest indication for induction in Foley's and PGE2 gel group was pregnancy induced hypertension which constituted 38.6% in group 1 and 37.1% in group 2.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations